Knowledge Description of Dental Clinic Student in RSGM Unsyiah about Ionizing Radiation and Negative Effect of Ionizing Radiation in Dental Radiography - Kemala Hayati; Cut Fera Novita; Susanti Angkat (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Radiology in medicine always involves ionizing radiation. Ionizing radiation in dentistry is used todiagnose, treatment planning, treatment, or lesion development monitoring. Dental radiography procedures mustbe carefully managed because X-rays radiation can damage healthy cells and tissues. The degree of radiation injuryis related to the total radiation dose, the proportion of body irradiated, the volume of tissues irradiated, and the timeinterval of the radiation dose received. This study was aimed to know about the knowledge description of dentalclinic students in RSGM Unsyiah about ionizing radiation and the negative effect of ionizing radiation in dentalradiography. The method of this study is a cross-sectional survey. The study included 254 dental clinic students atRSGM Unsyiah who fulfill inclusion criteria. Subjects were asked to fill questioner about ionizing radiation and thenegative effect of radiation in dental radiography. The result of that study shows that knowledge of dental clinicstudents about ionizing radiation (27,1%) dental clinic students had deficient knowledge, (46,4%) dental clinicstudents had sufficient knowledge, (26,3%) dental clinic students had a good understanding and knowledge ofdental clinic student about negative effect ionizing radiation in dental radiography (15,7%) dental clinic student haddeficient knowledge, (62,2%) dental clinic student had sufficient knowledge, (22%) dental clinic student had goodknowledge. The conclusion of this study showed that knowledge of dental clinic students about ionizing radiationand the negative effect of ionizing radiation in dental radiography is sufficient. KEYWORDS: ionizing radiation, negative effect ionizing radiation, dental radiography